MODEL OF COLLABORATION BETWEEN SUPPLIER AND MANUFACTURER FOR THE PROFIT OF SUPPLY CHAIN - Romenor, Muhammad Rafaee (Universiti Teknologi Petronas, 2012)
A world class supply chain management involves value-adding activities in the supplying process which to deliver the supplying service at its' optimal total cost, the least lead time and at the highest quality. At the highest level, supply chain system can he divided into two: (I) Production planning and inventory control and (2) Logistics process. The development of this model is based on the reviews on journals and compilation ofsmveys such as Pahl et al. (2007) and Li et al. (2010). Both surveys were discussing about recent interests of area of research about deterioration constraints in inventory. For deterioration constraint, Ghare and Schrader (1963) had introduced a common function to describe deteriorating inventory. Chakrabarty et al. (1998) extend Philips model using three parameters Weibull distribution whereas Wee ( 1999) using two parameters Weibull in addition by incorporating quantity discount and partial backordering. Wee et al. (2005) has developed a joint strategy for supplier and buyer under deteriorating constraint. Hou et al. (2009) also presented deterioration model using continuous discount cash flow to simulate the effect of inflation and permissible delay. Tripathi et al. (2010) extends Hou's (2009) model by developing a mathematical model for non-deteriorating model. In this project, the mathematical model is derived from inventory functionofGhare (1963) and incorporates economic constraints such inflation and permissible delay from Tripathi et al. (20 1 0), partial derivation of quantity discount from Benton (2007), order processing lead time reduction as per Huang et al. (2010) and effect of deterioration in supplier's inventory from Wee (1999). The new model presented in this project shall determine the optimal solutions in term of minimum present value of joint total cost can be achieved under constraints as mentioned above.